2005
DOI: 10.2166/wst.2005.0477
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of wastewater containing high phenol concentrations using stabilisation ponds enriched with activated sludge

Abstract: Treatment of wastewater containing high phenol concentrations (up to 4,000 mg/l, 1,600 kg/ha.d) in laboratory-scale stabilisation ponds enriched with activated sludge was studied. Phenol was biodegraded efficiently, even when fed as the sole carbon source. At influent concentrations of 1,000, 1,300, 1,600, 1,900, 2,500, 3,000 and 4,000 mg/l of phenol (loading rates of 400, 520, 640, 760, 1,000, 1,200 and 1,600 kg phenol/ha.d), the phenol removal efficiencies were 92, 89, 81, 81, 76, 65 and 22%, respectively. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In a study undertaken by Ramos et al using the laboratory scale facultative stabilization pond in which wastewaters with high phenol content was used for removal of phenol with different concentrations, the results showed that the highest and lowest rates of phenol removal relates to 1,000 mg/L (92%) and 4,000 mg/L (22%) concentrations, respectively [28]; but for the anaerobic pond for phenol removal no independent study was found. Results of the study by Nahid et al showed that by the increase in concentrating phenol within the range 0-200 mg/L, the COD removal rate is reduced due to the phenol toxicity effect on the microbial mass activity [29].…”
Section: Resultsmentioning
confidence: 99%
“…In a study undertaken by Ramos et al using the laboratory scale facultative stabilization pond in which wastewaters with high phenol content was used for removal of phenol with different concentrations, the results showed that the highest and lowest rates of phenol removal relates to 1,000 mg/L (92%) and 4,000 mg/L (22%) concentrations, respectively [28]; but for the anaerobic pond for phenol removal no independent study was found. Results of the study by Nahid et al showed that by the increase in concentrating phenol within the range 0-200 mg/L, the COD removal rate is reduced due to the phenol toxicity effect on the microbial mass activity [29].…”
Section: Resultsmentioning
confidence: 99%